Electrochemical investigations of Nb2O5/carbon materials from filter paper, microfibrillated and bacterial celluloses by sustainable reductive mineralization. (1st August 2019) - Henry, Aurélien; Le Vot, Steven; Alauzun, Johan G.; Hesemann, Peter; Foresti, Maria L.; Cerruti, Patricia; Heux, Laurent; Fontaine, Olivier; Boury, Bruno
Abstract: Cellulose is an attractive reagent for the elaboration of C-containing materials, but here, we also considered it as an O-provider for preparing macro, micro and nano-fibrous Nb2 O5 /C composites by a new mineralization with Nb2 Cl10 in anhydrous conditions. Our study highlights differences of reactivity between filter paper, microfibrillated or bacterial cellulose in connection with the crystallinity and the accessibility of the hydroxyl groups. The Nb2 O5 /C ratio was found to be adjustable (55–75% of Nb oxide) depending on the cellulosic precursor. Our composites were tested as electrodes that could be used as negative electrode in hybrid lithium-capacitor. Electrochemical characterizations of Nb2 O5 /C composites are reported and it was demonstrated that characteristics of the starting cellulosic reagents that influence physico-chemical properties of composites thus impact electrodes performances. Very interestingly, for 1C charging/discharging rates, capacities as good as thus of literature (150 mAh g −1 ) were obtained using our new sustainable synthesis protocol.